Establishing the acceptability and usability of an animated virtual patient simulation - Charlotte Lucy Richardson; Stephen Chapman; Simon White (Elsevier, 2021)
Background: An animated, video-based, virtual patient (VP) has been developed to allow pharmacists to learn how, and practice how, to advise patients taking non-vitamin K oral anticoagulants, a group of high-risk medicines. VPs are well-established resources but have historically only been accessed within specific online teaching sessions or at university sites; this new VP represents a mobile design that can be accessed from anywhere. Objective: To investigate the usability and acceptability of the VP application with a focus on exploring perspectives on accessibility. Methods: The study used an exploratory sequential mixed method design consisting of a satisfaction survey and interviews. Survey data were analysed descriptively to assess satisfaction with the application and to identify interview discussion areas. Interview data were analysed using the Framework Approach to thematic analysis. Participants were hospital or community pharmacists, or pre-registration pharmacists. Results: A total of 94 survey responses were collected and 22 respondents went on to take part in an interview. Participants reported liking the concept and delivery of the VP, particularly the high-quality technology. They also reported finding it usable, and appeared to favour its mobility and accessibility, particularly as the VP can be used on any internet accessible device, including mobile phones, with no specific requirements. Amendments that were suggested included quickening the delivery of some animations and improving navigation within the application, possibly through a button to return to the previous step should a mistake be made. Conclusions: The mobile VP appeared to be functional and usable, with the majority of users reporting satisfaction with use across a range of devices. Users reported positively about the VP's remote access, but navigation around the application requires development.